Synthesis of Chiral Polyamides Containing an (R, R)‐1, 2‐Diphenylethylenediamine Monosulfonamide Structure and Their Application to Asymmetric Transfer Hydrogenation Catalysis. Issue 3 (23rd January 2017) - Itsuno, Shinichi; Takahashi, Shotaro
Abstract: A chiral main‐chain polyamide containing an ( R, R )‐1, 2‐diphenylethylenediamine monotoluenesulfonamide (TsDPEN) repeating unit was prepared. Polycondensation of dicarboxylic acid dichloride with the chiral bisaniline of N ‐ tert ‐butoxycarbonyl‐protected TsDPEN was successful and afforded a chiral polyamide with a TsDPEN repeating unit as the chiral ligand structure. Treatment of the main‐chain polymer chiral ligand with transition‐metal complexes, such as [IrCl2 Cp*]2 (Cp*=η 5 ‐pentamethylcyclopentadienyl), [RhCl2 Cp*]2, and [RuCl2 ( p ‐cymene)]2, afforded polymer chiral metal complexes. Asymmetric transfer hydrogenation of a cyclic sulfonamide was efficiently catalyzed by the chiral TsDPEN polymer–metal complex to give an optically active cyclic sulfonylamine with quantitative conversion and high enantioselectivity. The polymer catalyst was easily recovered from the reaction mixture and reused several times without any loss in catalytic activity or enantioselectivity. Abstract : It DPENs on the ligand : Asymmetric transfer hydrogenation of a cyclic sulfonamide is efficiently catalyzed by a chiral ( R, R )‐1, 2‐diphenylethylenediamine monotoluenesulfonamide (TsDPEN) polymer–metal complex to give an optically active cyclic sulfonylamine with quantitative conversion and high enantioselectivity. The polymer catalyst can be easily recovered and reused several times without any loss in catalytic activity or enantioselectivity.